Analisis Pengaruh Profesionalisme Dan Kompetensi Pegawai Terhadap Kualitas Pelayanan Publik Pada Kantor Kelurahan Harapanmulya Kota Bekasi - Baskoro, Gerry Agung; Arumbinang, Nimas Ayu; Safrudin (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
The purpose of this study is to analyze the influence of Professionalism and Competence on the Quality of Public Services, the sample in this study was the Harapanmulya Village Community with a total of 117 respondents using an accidental sample. The analysis used in this study is Multiple Linear Regression Analysis. The results of this study indicate that Professionalism and Competence have a positive and significant effect on the Quality of Public Services by obtaining the results of a regression analysis of R Square (R2) of 0.685 or 68.5%. While 31.5% is influenced by other factors that are not included in this study such as motivation, reward and punishment, work environment, organizational culture and other factors.